Penerapan Metode Mind Mapping untuk Meningkatkan Hasil Belajar Kognitif Matematika Mahasiswa - Sabrun, Sabrun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The purpose of this research is to improve students' mathematics learning outcomes in low grade mathematics education subjects using the mind mapping method. The hypothesis of action research is that if the mind mapping method is used it can improve student cognitive learning outcomes. This research is classroom action research. The design of this research is based on Kemmis and Taggart using a spiral system. Each cycle consists of planning, implementation, observation and reflection. The results of this study were seen from the increase in student cognitive learning outcomes in cycle 1, namely 70.97% and the increase in cycle II changed to 90.32%. Based on the results of the observational analysis, there was an increase in the learning process, from 80% of the descriptors that were implemented to 95% of the descriptors that were implemented. Based on the data above, it can be concluded that the mind mapping method can improve students' cognitive learning outcomes in low grade mathematics subjects.